Implementation of urban public policies and gentrification processes. Santa Cruz case, Miraores - Tagle Argumanis , Eduardo Jesús (2024)
This research attempts to measure the impacts of urban public policies of local governments. All urban public policies implement transformation processes in the economic and social division of the intervened spaces. It almost always involves a deterioration in the living conditions of displaced groups, due to the gentrification processes generated. This article initially presents the context of the place of study and then an updated theoretical discussion of the concept of gentrification is carried out, understanding that it is a consequence of neoliberal public policies. This discussion is evaluated within two typical dimensions of the processes of gentrification, inequality and violence, and both are intertwined within the imaginary. In the years 2006 and 2007, urban public policies to update regulations were implemented in Miraflores, generating, in some sectors such as the Santa Cruz urbanization, improvements in the quality of life standards of residents, however, these regulations could be generating processes of gentrification.